Phytotherapies in motion: French Guiana as a case study for cross-cultural ethnobotanical hybridization - M.-A. Tareau; A. Bonnefond; M. Palisse; G. Odonne (BMC, 2020)
Abstract Background French Guiana is characterized by a very multicultural population, made up of formerly settled groups (Amerindians, Maroons, Creoles) and more recent migrants (mostly from Latin America and the Caribbean). It is the ideal place to try to understand the influence of intercultural exchanges on the composition of medicinal floras and the evolution of phytotherapies under the effect of cross-culturalism. Methods A combination of qualitative and quantitative methods was used. Semi-directive interviews were conducted in 12 localities of French Guiana's coast between January 2016 and June 2017, and the responses to all closed questions collected during the survey were computerized in an Excel spreadsheet to facilitate quantitative processing. Herbarium vouchers were collected and deposited at the Cayenne Herbarium to determine Linnaean names of medicinal species mentioned by the interviewees. A list of indicator species for each cultural group considered was adapted from community ecology to this ethnobiological context, according to the Dufrêne-Legendre model, via the "labdsv" package and the "indval" function, after performing a redundancy analysis (RDA). Results A total of 205 people, belonging to 15 distinct cultural groups, were interviewed using semi-structured questionnaires. A total of 356 species (for 106 botanical families) were cited. We observed that pantropical and edible species hold a special place in these pharmacopeias. If compared to previous inventories, 31 recently introduced species can be counted. Furthermore, this study shows that the majority of the plants used are not specific to a particular group but shared by many communities. However, despite this obvious cross-culturalism of medicinal plants between the different cultural communities of French Guiana, divergent trends nevertheless appear through the importance of 29 indicator/cultural keystone species in 10 cultural groups. Finally, we have emphasized that the transmission of herbal medicine's knowledge in French Guiana is mainly feminine and intra-cultural. Conclusion French Guianese medicinal flora is undoubtedly related to the multiple cultures that settled this territory through the last centuries. Cultural pharmacopeias are more hybrid than sometimes expected, but cultural keystone species nevertheless arise from a common background, allowing to understand, and define, the relationships between cultural groups.